Kegiatan Literasi Berbasis Pendekatan Montessori di SD Kanisius Sorowajan Yogyakarta - Gregorius Ari Nugrahanta; Eko Hari Parmadi; Paulus Mamok Suparmo; Hilary Relita Vertikasari Sekarningrum; Ni Kadek Swandewi; Fransiska Tyas Virya Prasanti (Universitas Lancang Kuning, 2022)
The decline in literacy skills and the character of students love of learning due to the COVID-19 pandemic at SD Kanisius Sorowajan Yogyakarta was the background for this community service activity. This activity aimed to improve reading and writing literacy as well as improve the character of students' enjoyment of learning by using the Montessori approach. The method used was Participatory Rural Appraisal involving teachers and grade 1 students. The results showed 1) there was an increase in literacy achievement in the ability to write cursive letters, cohesiveness of each letter, accuracy, completeness, and proportionality of each letter, layout accuracy, and completeness in copying and read stories. 2) There was an increase in the character of love of learning from pretest to posttest significantly by 44.162% with p = 0.000 (p < 0.05) which was included in the large effect category r = 0.9636 with an effectiveness level of 60.84%.